2021
DOI: 10.1002/nop2.993
|View full text |Cite
|
Sign up to set email alerts
|

The barriers and facilitators of foot care practices in diabetic patients in Indonesia: A qualitative study

Abstract: Diabetes mellitus (DM) is a chronic disease and a major health problem globally. Estimates suggest that in 2019, there were 63 million people in the world living with DM and that number is expected to rise to 578 million by 2030 and 700 million by 2045 (International Diabetes Federation, 2019). In Indonesia, there are approximately 10.7 million people living with DM in 2019 and that number is predicted to rise to 13.7 million in 2030, and 16.6 million by 2045 (International Diabetes Federation, 2019). An incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 57 publications
(56 reference statements)
3
29
0
Order By: Relevance
“…The overall management of a patient with diabetic with DFU needs an integrated approach that includes the involvement of a clinician, a podiatrist, counsellors, foot care nurses, a dietician, physiotherapists and so on to holistically manage the diabetic feet and optimise glycaemic control. This was also mentioned in several other studies supporting the approach of having a multiteam approach in the management of patients with DM and foot care 20 21. HCWs attitudes towards patients can also affect the quality of foot care they give.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The overall management of a patient with diabetic with DFU needs an integrated approach that includes the involvement of a clinician, a podiatrist, counsellors, foot care nurses, a dietician, physiotherapists and so on to holistically manage the diabetic feet and optimise glycaemic control. This was also mentioned in several other studies supporting the approach of having a multiteam approach in the management of patients with DM and foot care 20 21. HCWs attitudes towards patients can also affect the quality of foot care they give.…”
Section: Discussionmentioning
confidence: 73%
“…This is worrisome because HCWs must have adequate scientific knowledge about DM, DFU and foot care so they can be confident in disseminating such information and advice to patients. They must also be able to demonstrate the correct techniques of foot care to patients and possess the skills and knowledge to conduct foot examinations in order to diagnose them based on their risk level of developing DFU 20–23. Two studies showed nurses possess more practical knowledge on DFU that theoretical knowledge 12 23.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found a lack of knowledge regarding DM and its management is a barrier to self-care [47][48][49]. This study found that subjects generally understood diabetes, its symptoms, and its management and did not consider their knowledge a barrier to management.…”
Section: Knowledge Attitudes and Beliefsmentioning
confidence: 66%